CYFRA 21-1 is an early predictor of chemotherapeutic effectiveness in advanced nonsmall cell lung cancer: An observational study. Issue 52 (December 2016) - Zhao, Tongwei; Jin, Ying; Mao, Guangyun; Wei, Yaping; Wu, Guoqing; Ye, Xiao; Zhou, Yonglie; Yuan, Guorong; Gao, Liang; Hong, Yupeng; Chen, Yun; Hong, Chaojin; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Serum cytokeratin 19 fragment (CYFRA21-1) has been found to be a useful prognostic marker in lung cancer. Previous studies have revealed that change in CYFRA21-1 synchronously predicted therapeutic effectiveness in advanced nonsmall cell lung cancer (NSCLC) after the second cycle of chemotherapy. The objective of this study was to investigate the early predictive value of percentage change in serum CYFRA21-1 from pretreatment to completion of the first cycle of chemotherapy for chemotherapeutic effectiveness in advanced NSCLC patients. Ninety-seven advanced NSCLC patients with elevated serum CYFRA21-1 level (≥3.8 μg/L), who received 2 platinum-containing drugs, were included in this retrospective study. Serum CYFRA21-1 had been assayed before and after the first cycle of chemotherapy. To evaluate the effectiveness of chemotherapy, patients were allocated to disease control (DC) and progressive disease groups. The percentage changes of serum CYFRA21-1 concentration before and after first-cycle chemotherapy that occurred in each group were evaluated for their ability to predict achievement of radiologic DC, that is, to predict therapeutic effectiveness. The percentage change of serum CYFRA21-1 and the prevalence of ≥5% weight loss were higher in patients with progressive disease than in those with DC. The differences in other clinical and pathological variables including age, sex, Eastern Cooperative Oncology Group (ECOG) performance status, cigarette smoking, histological type, gross type, clinical stage, and chemotherapy regimens of the 2 groups were not significant. Both multiple generalized linear model analysis and linear trend tests indicated that the percentage change of serum CYFRA21-1 concentration was independently and negatively linked to the effectiveness of chemotherapy for NSCLC ( P < 0.01). The area under the receiver-operating characteristic curve of the percentage change in prediction of DC was 0.84 and the optimal cut-off value was17.5% ( P < 0.001). The percentage change of serum CYFRA21-1 after completing the first cycle of chemotherapy was predictive of treatment effects and might be helpful in making early decisions to change chemotherapy regimens in patients with advanced NSCLC.